Three Young Pioneers : A Story of the Early Settlement of Our Country - Mueller, John Theodore, 1885-1967 (Salt Lake City, UT : Project Gutenberg, 2009)
"Three Young Pioneers" by John Theodore Mueller is a historical novel written in the early 20th century. The story is set during the early settlement of America, following the journey and experiences of two orphaned siblings, Fred and Agnes, who are taken in by a kind-hearted couple on their way to America. As the narrative unfolds, the children navigate the complexities of pioneer life while grappling with their past and building new relationships in their new home. The opening of the story introduces the characters aboard a ship in the year 1630, marking their journey to America. After the death of their mother, Fred and Agnes are left orphaned and frightened among a group of settlers. However, they find solace and guardianship with Clara Bradley, who mourns her own longing for children. As the tale begins, the atmosphere is marked by the hardships of the journey across the Atlantic, the hope for a new life in America, and the close-knit community of settlers who support one another in a time of peril. This sets the stage for their adventures as they grow up in the Massachusetts Colony, learning to thrive amidst challenges and dangers. (This is an automatically generated summary.)
Release date is 2009-02-24
Produced by Jim Ludwig
Keywords: Puritans -- Juvenile fiction; Massachusetts -- History -- Colonial period, ca. 1600-1775 -- Juvenile fiction